Water-soaking effect and influence of nanoclay on mechanical properties of bamboo/glass fiber reinforced epoxy hybrid composites - Syed Mansoor Ahmad; Gowrishankar M. C.; Manjunath Shettar (Cogent Engineering, 2024)
AbstractFiber-reinforced polymer composites (FRPs) experience exposure to diverse environments throughout their intended design life. Investigating the aging process of FRPs immersed in water is crucial for enhancing the material’s durability. In this study, glass fiber, bamboo fiber, nanoclay and epoxy composites are produced using the hand lay-up process. Tensile and flexural tests are performed in adherence to ASTM standards. The water uptake percentage of soaked specimens is computed, and a comparison is drawn between the results of dry and water-immersed composite specimens. Water-soaking condition negatively affects all the composites. Water-soaked specimens exhibit lesser tensile and flexural strengths than dry specimens by 7.4–14.8% and 7–13.6%, respectively. The addition of nanoclay further improves the tensile and flexural strengths of epoxy and all composites by 6–11%. Water uptake (%) and water-soaking effects on the strength of composites decline when nanoclay is added. The addition of nanoclay declines the percentage of reduction of tensile strength from 8.6–14.8% to 7.4–12%. Similarly, the percentage of flexural strength reduction declines from 8–13.6% to 7–11%. The dry and water-soaked specimens’ fracture surfaces (Scanning Electron Microscope [SEM] images) show significant variations.